Biphasic effects of Callicarpa nudiflora water extract on rumen fermentation in vitro and microbial communities in sheep - Wanqin Yang; Wanqin Yang; Runhang Li; Wenxi Wang; Kunna Li; Yiying Huang; Ying Ying; Yuning Liu; Hongxin Wu (Frontiers in Animal Science, 2025)
IntroductionThis study investigated the effects of varying doses of Callicarpa nudiflora water extract (CW) on in vitro rumen fermentation and sheep microbial activity.MethodsFour rumen-cannulated hybrid sheep were selected to provide mixed rumen fluid, and the powder substrate remained consistent with the diet fed to the sheep. A total of 14 supplementation levels (0–25 g/kg fresh substrate) of CW were designed based on a completely randomized design, including 0, 0.5, 1, 2, 3, 4, 6, 8, 10, 12, 14, 16, 20 and 25 g/kg. Each treatment was replicated in duplicate across three independent batches, resulting in a total of six biological replicates per treatment. The flasks were incubated at 39°C for 24 hours in water with a rotation speed of 80 r/min.ResultsIt showed that adding CW significantly affected in vitro rumen fermentation in sheep and displayed a biphasic action: The supplementation levels of 4 g/kg and 6 g/kg showed an improvement in the fermentation status and nitrogen utilization efficiency with the enhanced microbial protein concentration from 1.98 mg/mL (Con) to 2.84 mg/mL (P < 0.001) and the relative abundance of total bacteria from 4.05 (Con) to 5.27 (P < 0.001); When the dose surpassed 14g/kg, the decline in the hemicellulose degradation rate from 63.00% (Con) to 40.24% (P < 0.001), accompanied by an increase in ammonia-nitrogen (NH3−N) concentration from 173.37 mg/L (Con) to 177.46 mg/L (P = 0.020) and total gas production from 154.87 mL/g (Con) to 161.47 mL/g (P =0.007), signaled abnormal alterations in the fermentation process.Conclusions The optimal supplementation range in feed formulations was established as 4−6g/kg, showing that CW could serve as a natural rumen modulator for sheep.